2023
DOI: 10.1111/cts.13495
|View full text |Cite
|
Sign up to set email alerts
|

Age associations with tacrolimus and mycophenolic acid pharmacokinetics in stable Black and White kidney transplant recipients: Implications for health inequities

Abstract: Tacrolimus (TAC) and mycophenolic acid (MPA) provide maintenance immunosuppression and is dosed empirically in elderly kidney transplant recipients (KTRs) resulting in health inequities. Limited immunosuppressive pharmacokinetics are available comparing adult ages. This secondary analysis compared TAC and MPA pharmacokinetics and adverse effects (AEs) among young, middleaged, and elderly Black and White KTRs. The 12-h TAC and MPA pharmacokinetics with AE evaluation were conducted in 67 stable KTRs greater than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Violette Gijsen investigated the effect of age on tacrolimus pharmacokinetics and reported similar results [21]. Another study found that the blood clearance rate of tacrolimus in the elderly is lower than that in the young, the possible reason is that liver aging leads to the decline of liver function, which affects the blood concentration of tacrolimus in the body [22]. Until more recently kidney transplantation was not recommended for elderly patients, but evidence has shown that older people who receive kidney transplantation have higher rates and lengths of survival than younger people [23].…”
Section: Discussionmentioning
confidence: 93%
“…Violette Gijsen investigated the effect of age on tacrolimus pharmacokinetics and reported similar results [21]. Another study found that the blood clearance rate of tacrolimus in the elderly is lower than that in the young, the possible reason is that liver aging leads to the decline of liver function, which affects the blood concentration of tacrolimus in the body [22]. Until more recently kidney transplantation was not recommended for elderly patients, but evidence has shown that older people who receive kidney transplantation have higher rates and lengths of survival than younger people [23].…”
Section: Discussionmentioning
confidence: 93%
“…39). Elderly KT recipients are characterized by higher TAC dose‐ and weight‐adjusted blood exposure, 40,41 notably explained by a reduced drug clearance itself resulting from the decline in liver function 42 . Therefore, age is a valuable factor integrated in some models of TAC population PKs 28,29,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Elderly KT recipients are characterized by higher TAC dose-and weight-adjusted blood exposure, 40,41 notably explained by a reduced drug clearance itself resulting from the decline in liver function. 42 Therefore, age is a valuable factor integrated in some models of TAC population PKs. 28,29,43 Additionally, the gut microbiota composition evolves with advancing age due to, among others, the deterioration of dentition (and subsequent changes in dietary habits) and the lowering of intestinal motility.…”
Section: Articlementioning
confidence: 99%